Removal of Methyl Violet from Aqueous Solutions Using the A Site Doped Perovskite +-Oxides BaxSr3-xNbO5.5 (x=0, 1 and 2) - Labib., A. Awin; Mahmoud., A. El-Rais; Abdunnaser, M Etorki; Moda., M. Ezrgane (Journal of New Developments in Chemistry, 2020)
Three members of the A- site doped Nb perovskites with general formula Sr3NbO5.5, BaSr2NbO5.5 and Ba2SrNbO5.5 were synthesised by solid-state methods and their removal efficiency of Methyl violet from aqueous solutions investigated. The X-ray diffraction measurements demonstrated that the three samples have a faced cubic perovskite-type structure in space group Fm m. The addition of Ba2+ into the A-site of Sr3NbO5.5 has influenced the cell volume, crystal size and density. Subsequently, the removal capacity was also impacted. The crystallite size of the oxides was determined to be less than 82 nm. The maximum removal capacities of Methyl violet are found to be 46.5, 13.1 and 8.0 mg/g using Ba2SrNbO5.5, BaSr2NbO5.5 and Sr3NbO5.5 respectively. The amounts of the dye adsorbed by the oxides have increased as the Ba2+ content increased. The removals of Methyl violet have positive relationship with pH, temperature and the mass of the oxides.
Keywords: Removal; Methyl violet; A-site Doping.